Labour, politics, and the state in industrializing Thailand - Brown, Andrew, 1953- (London ; New York : RoutledgeCurzon, 2004)
This book focuses on how the state has become entangled in the processes through which workers have been organized, reorganized and disorganized as social and political actors in different historical periods.
Monarchs, workers, and struggles for a voice -- The 1932 coup d'état, political volatility, and labour's fluctuating fortunes -- Radicalism, shifting alliances, and managing labour's political space -- Capitalist expansion, regime dynamics, and the rise of enterprise unionism -- Export-oriented industrialization, battles for the state, and the disorganization of organized labour -- Organizing labour in the 1990s: crisis and continuing struggles for a political voice.
Includes bibliographical references (pages 151-166) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Working class -- Thailand -- History -- 20th century; Labor unions -- Thailand -- History -- 20th century; Labor unions -- Political activity -- Thailand -- History -- 20th century; Industrialization -- Thailand -- History -- 20th century; Travailleurs -- Thaïlande -- Histoire -- 20e siècle.; Syndicats -- Thaïlande -- Histoire -- 20e siècle.; Syndicats -- Activité politique -- Thaïlande -- Histoire -- 20e siècle.; Industrialisation -- Thaïlande -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Industrialization; Labor unions; Labor unions -- Political activity; Working class; Thailand; 1900-1999; Electronic books; History